Two Settlement Pathways for Gross Violations of Human Rights Based on The Dignified Justice Theory - Teguh Prasetyo; Jeferson Kameo (Mimbar Keadilan, 2024)
Settlement of gross violations of human rights might be pursued by choosing two “paths” provided. The first “path” is via the Human Rights Court. This route is also called litigation settlement. The second path is an alternative “path”, and has been coined as the out of the Human Rights Court settlement. The problem is the Constitutional Court states that the alternative “path” as referred to in the Explanation of Article 47 of the Law on Human Rights Courts is contrary to the Constitution. As a result of the issuance of the Constitutional Court decision, the alternative “path” seems to be in a state of limbo, and this presupposes a legal issue of the lack of clarity on the meaning of a formulation of the applicable statutory provisions. In this paper, it is argued that Article 47 of the Law on Human Rights Courts still recognizes two “paths” for solving or settling cases of gross violations of human rights in the Pancasila legal system. The research method used in this paper is normative legal research, often known as the pure legal research method. It examined the primary legal materials. The theory used for understanding and explaining the problem is the Dignified Justice theory, the Indonesian Jurisprudence.